(untitled) (PANGEEA, 2025)
Considerations about Karst of Vaşcău Plateau. Caves and their features exist in an environment with no natural light and contain a myriad of physical and psychological obstacles Systematic cave exploration is a two-fold process that involves the physical pursuit and discovery of caves and cave systems, and field documentation that provides baseline data in the form of cave survey data and notes, cave entrance and cave/karst feature locations and inventories, written observations, and documentation. The present paper wish to contribute with an inventory of caver from the Vascau Plateau – Codru Moma Mountains.